Intensification of thermal energy storage using copper-pentaerythritol nanocomposites for renewable energy utilization. (January 2021) - Mani, Dineshkumar; Saranprabhu, M.K.; Rajan, K.S.
Abstract: Pentaerythritol is a solid-solid phase change material with a high enthalpy of solid-solid phase transition (260–280 kJ/kg) and low thermal conductivity (0.2–0.7 W/mK). Thus, it is imperative to improve the thermal conductivity of pentaerythritol. The use of copper nanoparticles as an additive to pentaerythritol is explored, resulting in the development of copper-pentaerythritol composites. The effect of key independent variables (concentration of copper nanoparticles = 0–0.25 wt%; temperature = 40–180 °C) influencing the thermophysical properties (thermal conductivity and enthalpy of solid-solid transition) of copper-pentaerythritol composites has been studied. Transient planar source method was used for the measurement of thermal conductivity, while differential scanning calorimetry was used for the measurement of specific heat and enthalpy of solid-solid transition. Copper-pentaerythritol composites possessed higher thermal conductivity than pure pentaerythritol and this could be attributed to phonon conduction and nanoparticle clustering. The composite containing 0.0625 wt% copper nanoparticles exhibited 14–22.5% enhancement in thermal conductivity with no loss of enthalpy for solid-solid phase transition. This resulted in the reduction of time for completion of the solid-solid phase transition by 35.8% and an increase in the rate of thermal energy absorbed by 35.6%. Highlights: Copper-pentaerythritol composites containing (0.0625–0.25 wt %) copper prepared. 22.5% increase in thermal conductivity at 180 ° C for 0.0625 wt % composite. Thermal conductivity increase is attributable to phonon conduction and clustering. 35.6% enhancement in rate of thermal energy absorbed for 0.0625 wt % composite. Composites were stable even after 1000 thermal cycles.